Validation of the Sysmex XN analyser and Blood Bank mode for the quality and safety of donor blood and transfusion products - Valina, Ondrej; Vankova, Ida; Mintzas, Konstantinos; Knappova, Klara; Gasova, Zdenka (Transfusion medicine, 2024)
OBJECTIVES: Our objective was to compare the measurement of residual white blood cell (rWBC) and residual red blood cell (rRBC) counts in blood products using the XN Blood Bank mode and the laboratory standard operating procedures for manual counts. In addition, to compare the whole blood complete blood count (CBC) values of blood donors and the quality of blood products using the Sysmex XN analyser versus the XS-1000i analyser. MATERIALS AND METHODS: For blood donors, 190 samples from blood or apheresis donors were analysed on both the Sysmex XS-1000i and XN-1000 analysers and the mean values of six CBC parameters were compared: the white blood cell count (WBC), the red blood cell count (RBC), haemoglobin (HGB), haematocrit (HCT), the mean corpuscular volume (MCV), the platelet count (PLT). For blood products, 164 samples were collected: 13 Plasma products - whole blood, 9 Plasma products - apheresis, 36 RBC concentrates - whole blood, 30 PLT concentrates - buffy coats, 36 PLT concentrates - buffy coats - pooled and 55 PLT concentrates - apheresis. RESULTS: All CBC parameters of the blood donors tested showed similar performance, with excellent correlation coefficients (r) ranging from 0.821 to 0.995. The majority of the blood products did not have a quantifiable number of residual cells, meaning the number of rWBC and rRBC, if present, was below the limit of quantitation (LoQ) of the different methods. rWBC were detected by Blood Bank mode in Plasma products - whole blood with a mean rWBC of 0.012 × 109 /L and in PLT concentrates - buffy coats with a mean rWBC of 0.19 × 109 /L. The correlation coefficient in both analysers for all three parameters (HGB, HCT, RBC) in RBC concentrates - whole blood was excellent, ranging from 0.95 to 0.99. For platelet count, r ranged from 0.98 to 0.99. CONCLUSION: The XN-Series analyser, equipped with a Blood Bank mode, demonstrated reliable performance when used for blood donor evaluation, rWBC enumeration and measurement of end blood products.
Keywords: krevní obraz; erytrocyty; Blood Donors; Blood Banks; krevní banky; lidé; Platelet Count; Erythrocytes; Blood Cell Count; dárci krve; počet trombocytů; Humans